Feasibility of screening for Chlamydia trachomatis in young men attending an emergency department. Issue 7 (23rd June 2008) - Sood, T; Sally, D; Spencer, N; Banerjee, A; Hinchley, G
Abstract : Objective: To determine the feasibility of screening asymptomatic young men for genital Chlamydia trachomatis infection in a suburban emergency department setting. Design: Prospective observational study. Setting: Chase Farm Hospital Emergency Department in Enfield, North London. Participants: Asymptomatic sexually active men aged 16–24 years. Methods: A convenience sample of men aged 16–24 years attending the emergency department was offered urine-based screening for Chlamydia at triage. Verbal consent was obtained and first pass urine specimens were tested using the strand displacement amplification technique. Participants were traced by their preferred method of contact in order to be offered treatment within 2 weeks of attendance at the emergency department. Results: 67 men participated, 64 of whom were tested, 3 returning positive tests. The prevalence of Chlamydia in asymptomatic men attending the emergency department was 4.7%. Conclusion: Urine testing for genital C trachomatis in the emergency department can identify asymptomatic men in the community who may otherwise remain undetected. It is suggested that this is a worthwhile screening test to offer in the emergency department, providing follow-up for treatment can be arranged locally. There is no requirement for increased emergency department input into these patients over and above introducing them to the screening programme.